American sociology : from pre-disciplinary to post-normal - Turner, Stephen P. (Palgrave Macmillan, 2020)
American Sociology has changed radically since 1945. This volume traces these changes to the present, with special emphasis on the feminization of sociology and the decline of the science ideal as well as the challenges sociology faces in the new environment for universities.